Challenges and solutions of participatory management in educational fields: education organization of Golestan state as a case study - Ghorbani, Ali Reza; Abdullah, Haslinda; Zolfaghari, Akbar; Jomenia, Sakineh (Faculty of Educational Studies, Universiti Putra Malaysia, 2009)
Today, the concept of participation is an important tool to improve the effectiveness of mangers in organizations. Participatory management has also to be introduced in which power is shared, everyone is given an opportunity to participate, work is conducted by consensus and multidisciplinary teams are utilized to implement processes. The type of management is one of the new phenomena that has emerged in recent years. Management confidence to staffs, distribution of decision making in planning and consultation, implementing the staffs' suggestions, communicative system, friendly space, participating of the staff in determination of styles of implementation the activities, monitoring and evaluation, noticing personal affairs, and flexibility in regulations are the major components of participatory management. The general goal of this paper is to investigate the managerial policies in the Education Organization of Golestan state in Iran. The particular goal of the paper is to find out the challenges faced by participatory management and also recognize its solutions to develop participatory management in this state.